Fathers' leave reduces sexist attitude - Tavits, M; Homola, J; Ward, D; Schleiter, P (Cambridge University Press, 2023)
Research shows that sexist attitudes are deeply ingrained, with adverse consequences in the socio-economic and political sphere. We argue that parental leave for fathers – a policy reform that disrupts traditional gender roles and promotes less stereotypical ones – has the power to decrease attitudinal gender bias. Contrasting the attitudes of new parents who were (and were not) directly affected by a real-world policy reform that tripled the amount of fathers’ leave, we provide causal evidence that the reform increased gender-egalitarian views in the socio-economic and political domains among mothers and fathers, and raised support for pro-female policies that potentially displace men among mothers. In contrast, informational, indirect exposure to the reform among the general public produced no attitudinal change. These results show that direct exposure to progressive social policy can weaken sexist attitudes, providing governments with a practical and effective tool to reduce harmful biases.